Co-constructing an essay: collaborative writing in class and on wiki - Ansarimoghaddam, Shokoufeh; Bee, Hoon Tan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This paper compares the quality of students’ individually written essays after they had gone through the processes of collaborative writing through wiki and face-to-face. The study employed a counterbalance research design. Participants of the study were thirty tertiary ESL students from one intact class. They were divided into two experiment groups with each comprising 15 students. Before the experiment, each participant wrote a pre-experiment essay. After that they were given two treatments of collaborative writing through wiki and face-to-face. The order of giving the two treatments was different for the two groups. After each treatment of collaborative writing, the participants wrote two argumentative essays in groups, and wrote two essays individually. After the experiment, a semi-structured interview was conducted as a triangulation measure. Results show that collaborative writing on wiki can be more effective than collaboration face-to-face in improving students’ essay writing.